Social implications of structural adjustment in the Caribbean: reference paper - Bourne, Compton (ILO. PREALC Port of SpainTT, 1991)
Provides a summary analysis of the recent economic performances of Caribbean countries to emphasize the urgency of the development problem. Identifies forces in the world economy which reinforce the need for structural adjustment of the Caribbean economy and outlines the main lines along which adjustment should proceed.